Health-related quality of life from the FALCON phase III randomised trial of fulvestrant 500 mg versus anastrozole for hormone receptor-positive advanced breast cancer - Robertson, John F.R.; Cheung, Kwok-Leung; Noguchi, Shinzaburo; Shao, Zhimin; Degboe, Arnold; Lichfield, Jasmine; Thirlwell, Jackie; Fazal, Mehdi; Ellis, Matthew J. (Elsevier, 2018)
Background The phase III randomised FALCON trial (NCT01602380) demonstrated improved progression-free survival with fulvestrant 500 mg versus anastrozole 1 mg in endocrine therapy-naïve postmenopausal women with hormone receptor-positive (HR+) locally advanced or metastatic breast cancer (LA/MBC). Furthermore, overall health-related quality of life (HRQoL) was maintained and comparable for fulvestrant and anastrozole. Here, we present additional analyses of patient-reported HRQoL outcomes from FALCON.